Impacto de la reforma colombiana de la seguridad social sobre la dinámica y características del aseguramiento en salud (1999)
ABSTRACT: One of the major aims of the social security reform of 1993 in Colombia was to increase the coverage of health services, which was estimated in only 75% prior to the approval of the Law 100 of 1993. The goal was to achive universal coverage by the year 2001, and for this purpose important changes were introduced in the traditional insurance and financing mechanisms of social security, so that official subsidies were reduced and the number of people affiliated through compulsory contribution was increased. These changes are part of general institutional reforms carried out by government and ruling grupos since the early 90's under the inspiration of social doctrines that seek to reduce the State's role in economic decisions and in the assignment of social resources. The primary objetive of the study was to determine the achievements in health insurance coverage in the whole country between 1995 and 1998 and some characteristics of this coverage. This is a descrptive retrospective study, in which qualitative and quantitative techniques of documentary research were used. Results show that health insurance coverage obtained through the General System of Social Security for Health until June 1998 was 49.1% of the whole population of the country. An unknown percentage ("población vinculada") has access to health services but hasn't been incorporated to the insurance mechanisms designed by the reform. This result is very distant form the universal coverage desired for year 2001. Adittionally, some indicators related to the persistence of inequalities in health among different regions of the country were found.